Utilitarian or entertainment? Value obtained from mobile phones by users in low socioeconomic strata in emerging markets. Issue 5 (23rd July 2020) - Maity, Moutusy
Abstract : Purpose: This research empirically investigates the differential roles of utility and entertainment on the value obtained from the use of mobile phones by users belonging to low-income groups in emerging markets. Design/methodology/approach: This research reports the findings from an investigation that obtains data through a survey of mobile phone users from urban and rural areas across five emerging markets. Structural equation modeling is used to analyze the data obtained. Findings: Study findings demonstrate that users obtain utility, social as well as entertainment value from mobile phones. Research limitations/implications: This investigation uses the capability approach for conceptualizing the capabilities obtained from mobile phones by users from lower socioeconomic strata, a theoretical lens that is particularly suited for explaining behavior that may represent well-being of the user group. Practical implications: Managers may explore whether the platform of entertainment is a suitable vehicle for offering additional services. This study's findings also suggest that creating value for customers should be a primary concern in emerging markets, similar to that in developed markets. Originality/value: This research is among a few that report investigations into the differential roles of utility and entertainment on the value obtained from mobile phones. This study also presents differences in terms of: urban versus rural, younger versus older and male versus female subgroups. This research presents a large-scale multicountry empirical study investigating mobile phone use by users from lower socioeconomic groups in emerging markets.